Insuring Hollywood: A movie returns index and the American stock market - Davide Lauria; Wyatt D. Phillips (Journal of Risk and Financial Management, 2021)
The aim of this paper is the definition of a daily index representing the risk-return on investments in the American film industry. The index should be used to predict the riskiness and the expected return of movie projects at the level of the overall industry and then to determine a premium for insurance for such an investment. Such an index can inform the decision making in relation to risk but also timing. Though not currently legal in the United States, such an index may be relevant at some point in the future or in other countries for film production companies as well as venture capitalists interested in investing in one or a slate of motion picture productions or more broadly in the holdings of a media conglomerate, an exhibition chain, or some other aspect of the media landscape.
Keywords: 330; American film industry; Hollywood; insurances; option pricing; returns index; ROI